CA-MRSA and Leptospirosis Co-Infections : The recipe to a Successful Management - Yeap, Boon Tat; Rajesh Kumar Muniandy (Gazi University, 2019)
Co-infection of leptospirosis and Community Acquired Methicillin Resistant Staphylococcus Aureus (CA-MRSA) in a healthy pregnant patient is extremely rare. We report a successful medical treatment of a young pregnant patient who presented to our institution with leptospirosis and CA-MRSA.